Investigation of apolipoprotein E and angiotensin-converting enzyme gene polymorphisms on serum lipid profile in Turkish coronary artery disease patients - (:unkn) unknown (My University, 2000)
Backround. An Insertion/Deletion (I/D) polymorphism in the gene for angiotensin-converting enzyme (ACE) has been associated with myocardial infarction and other cardiac pathology. Because CAD is influenced by the apolipoprotein E (Apo E) genotype, the possibility of a relationship between ACE and apo E genotypes and CAD was also sought. Methods. We investigated possible relations between ACE I/D and apo E gene polymorphism and coronary artery disease in 58 CAD patients and 69 healthy controls. Serum lipid levels were measured enzymatically. Polymerase Chain Reaction (PCR), Restriction Fragment Length Polymorphism (RFLP), and agarose gel electrophoresis techniques were used to determine the ACE and apo E genotypes. Results. Apo ε4 allele was significantly higher in the CAD group than in the control group (p<0.05). The frequency of deletion alleles (D) was higher in the CAD group than in the control group (p<0.01). Subject with an ε2 allele had the lowest levels of TC (p<0.05), and LDL-C (p<0.01), while subjects with the ε4 allele had the highest. This result suggest that high level TC and LDL-C can further contribute to the cardiovascular risk in ε4-individuals. The distribution of the lipoprotein parameters such as TC, triglyceride HDL and LDL did not differ between the genotypes of ACE (p>0.05). Conclusion. Our data provided additional support to the hypothesis that bearers of apo ε4 and ACE D alleles are predisposed to the development of cardiovascular diseases, while subjects carrying the apo ε2 and ACE I alleles are apparently protected. Such results are precontinued interest in and a potent greater role for measurement of a alleles and other genetic lipid in the future.